Folklore and Zooarchaeology: Nonhuman Animal's Representation in the Historical Narrative - (:unkn) unknown (My University, 2024)
It has been argued before that archaeology and folklore go hand-in-hand, with a variety of scholarship and studies focusing on landscapes and monuments in reference to this pair; however, this research argues for a different approach. As the title suggests, this paper engages with folklore topics and zooarchaeological data to argue that faunal remains (along with landscapes and monuments) are intertwined and cannot be separated from the historical narrative. While faunal evidence helps provide scientific explanations of the natural interconnectedness of humans and nonhuman animals, folklore aids in creating and developing cultural understandings. By exploring the relationship between humans and animals, this paper examines faunal analysis and folklore evidence to argue that animals have contributed more to human history than just fodder for the human diet and roles in subsistence economies.
Keywords: folklore; zooarchaeology; storytelling; material culture; faunal remains; nonhuman animals